The association between indoor air quality and respiratory health symptoms among preschool children in Penang, Malaysia - Azam, Nur Syazura Akmal; Jalaludin, Juliana; Suhaimi, Nur Faseeha (Taylor and Francis, 2024)
A cross-sectional study was conducted among 126 preschool children aged 4–6 years in traffic, industrial, and suburban areas of Penang, Malaysia, to determine their exposure to indoor air pollutants and their associations with respiratory symptoms. A standardised and validated questionnaire was used to collect data on respiratory health symptoms among respondents. An indoor air quality assessment was conducted in selected preschools that included temperature, relative humidity, air velocity, volatile organic compounds (VOCs), and particulate matter (PM2.5, and PM10). There were significant differences in median concentrations of PM2.5, PM10 and relative humidity among study groups. Statistical analysis showed significant associations between air pollutants in preschool with respiratory symptoms. Factors that influenced the increased likelihood of cough and phlegm were linked to the increase in PM2.5 exposure. This study suggests regular classroom cleaning and routine maintenance of air conditioners to be done inside the preschools.